Linking Customer Justice Perception, Customer Support Perception, and Customer Citizenship Behavior to Corporate Reputation: Evidence from the Airline Industry - Cintamur, Ismail Gokhan (Palgrave Macmillan Ltd, 2023)
By applying the equity theory, organizational support theory, signaling theory, and the social exchange theory to the customer context, this study intends to investigate the antecedents and consequences of service customers' corporate reputation evaluation by examining the direct and indirect relationships between customers' corporate reputation evaluation, customer justice perception, customer support perception, and customer citizenship behavior. Self-administered online surveys were conducted by implementing snowball sampling among real airline customers in Turkey, and 741 valid surveys were collected. Direct and indirect relationships between the research variables were tested via structural equation modeling and bootstrapping methods. Results showed that distributive justice perception, interactional justice perception, and customer support perception positively affect customers' corporate reputation evaluation, whereas customers' corporate reputation evaluation positively affects customer citizenship behavior as well. Furthermore, it was found that customers' corporate reputation evaluation has a mediation role in the relationships between distributive justice perception, interactional justice perception, customer support perception, and customer citizenship behavior.
Keywords: Customer Justice Perception; Customer Support Perception; Corporate Reputation; Customer Citizenship Behavior; Equity Theory; Organizational Support Theory; Signaling Theory; Social Exchange Theory; Perceived Organizational Support; Social-Exchange Theory; Co-Creation Behavior; Scale Development; Moderating Role; Satisfaction; Performance; Impact; Personality; Validity